2023
DOI: 10.3389/fneur.2023.989974
|View full text |Cite
|
Sign up to set email alerts
|

Blood biomarkers of secondary outcomes following concussion: A systematic review

Abstract: IntroductionBlood biomarkers have been identified as an alternative tool for predicting secondary outcomes following concussion. This systematic review aimed to summarize the literature on blood biomarkers of secondary outcomes following concussion in both pediatric and adult cohorts.MethodsA literature search of Embase, Medline and PubMed was conducted. Two reviewers independently assessed retrieved studies to determine inclusion in systematic review synthesis.ResultsA total of 1771 unique studies were retrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…In our study, compared to patients without PND, PND (+) patients had an increasing of S100B serum level after TAAR with a peak concentration right after surgery and returned to normal level 24–48 h after surgery, which was consistent with previous studies (Tables S7 , S8 ) 30 , 31 . TAU protein is a microtuble-associated protein found in neurons and is a biomarker for neurodegeneration 32 , 33 . In an observational study of long-term persistent elevation of neurodegeneration markers after cardiac surgery, researchers found that serum levels of TAU protein increased 24 h after surgery and remained elevated at 7 days and three months for patients with neurodegeneration 34 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, compared to patients without PND, PND (+) patients had an increasing of S100B serum level after TAAR with a peak concentration right after surgery and returned to normal level 24–48 h after surgery, which was consistent with previous studies (Tables S7 , S8 ) 30 , 31 . TAU protein is a microtuble-associated protein found in neurons and is a biomarker for neurodegeneration 32 , 33 . In an observational study of long-term persistent elevation of neurodegeneration markers after cardiac surgery, researchers found that serum levels of TAU protein increased 24 h after surgery and remained elevated at 7 days and three months for patients with neurodegeneration 34 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GFAP is a protein that found in astrocytes and is released into the bloodstream following brain injury, and it has a high specificity and sensitivity of neurological damages 32 . Nurcahyo et al examined GFAP serum levels for patients with and without postoperative cognitive dysfunction (POCD) after on-pump coronary artery bypass grafting 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation